Optimizing irrigation and nitrogen fertilization for winter wheat using the AquaCrop model and water footprint analysis - JIA Yifan; WANG Hao; HAN Ce; XU Zhenghe; LIU Yuyu (Guan'gai paishui xuebao)
【Objective】Nutrient and water interactions play a crucial role in their uptake by crops. Understanding their optimal combination is essential for improving the efficiency of their use. This paper presents a method for optimizing irri-gation strategies for winter wheat production under varying nitrogen application rates in different hydrological years using the AquaCrop model. By integrating water footprint theory, we evaluate the water-fertilizer coupling under various scenarios.【Method】The study was conducted at the Weishan Irrigation District, where field experimental data were used to calibrate the AquaCrop model. The calibrated model was then used to simulate changes in winter wheat yield, aboveground biomass, and other crop traits. A total of 76 irrigation schemes under three nitrogen application rates were considered to determine optimal irrigation strategies for a typical hydrological year. Water footprint analysis was conducted using a soil moisture dynamic balance model to evaluate the sources of water uptake by the crop.【Result】The optimal irrigation schemes were determined based on dual objectives: high yield and irrigation water use efficiency. At a nitrogen application of 218 kg/hm2, the optimal irrigation strategy was as follows: In the wet year (2008—2009), irrigating during the jointing and filling stages, with a total irrigation amount of 108 mm. In the normal year (2019—2020), irrigating during the heading and filling stages, with a total irrigation amount of 162 mm. In the dry year (2012—2013), irrigating during the heading and filling stages, with a total irrigation amount of 136 mm. The optimal irrigation strategy for nitrogen applications of 198 and 178 kg/hm2 was similar to that for 218 kg/hm2.【Conclusion】Under water-limited conditions, prioritizing irrigation during the heading and filling stages of winter wheat maximizes benefits. Across all scenarios, the green water footprint predominated, while the blue water footprint played a supplementary role during the jointing, heading, and filling stages. The contribution of blue water was lowest in wet years and higher in both normal and dry years.